Clickable Periodic Mesoporous Organosilicas: Synthesis, Clickability and Adsorption of Antibiotics - Gao, J.; Zhang, X.; Xu, S.; Tan, F.; Li, X.; Zhang, Y.; Qu, Z.; Quan, X.; Liu, Jian (Wiley - V C H Verlag GmbH & Co. KGaA, 2014)
Pharmaceutical antibiotics are not easily removed from water by conventional water-treatment technologies and have been recognized as new emerging pollutants. Herein, we report the synthesis of clickable azido periodic mesoporous organosilicas (PMOs) and their use as adsorbents for the adsorption of antibiotics. Ethane-bridged PMOs, functionalized with azido groups at different densities, were synthesized by the co-condensation of 1,2-bis(trimethoxysilyl) ethane (BTME) and 3-azidopropyltrimethoxysilane (AzPTMS), in the presence of nonionic-surfactant triblock-copolymer P123, in an acidic medium. Four different alkynes were conjugated to azide-terminated PMOs by means of an efficient click reaction. The clicked PMOs showed improved adsorption capacity (241 micrograms g-1) for antibiotics (ciprofloxacin hydrochloride) compared with azido-functionalized PMOs because of the enhanced pie–pi stacking interactions. These results indicate that click reactions can introduce multifunctional groups onto PMOs, thus demonstrating the great potential of PMOs for environmental applications.